2014
DOI: 10.1177/0267323114545710
|View full text |Cite
|
Sign up to set email alerts
|

24 hours of an #outcry: The networked publics of a socio-political debate

Abstract: This article explores the development of a social–political discussion on everyday sexism in Germany, labelled ‘#aufschrei’ (German for ‘outcry’), that started as a small Twitter conversation and evolved into a nationwide debate within 24 hours. After discussing the relationship of social actions, social networks and interlinked digital objects in the construction of networked publics, the authors propose to understand #aufschrei as an ‘ad hoc’ public – a communication sphere evolving around a shared topic wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 22 publications
0
18
1
1
Order By: Relevance
“…Anstead and O'Loughlin (2011) revealed that 20% of those commenting on a TV program on Twitter were responsible for more than 50% of the content. Maireder and Schlögl (2014) reconstructed the dynamics of a debate about sexism in Germany, examining the hashtag #aufschrei (#outcry) to visualize networked publics, mapping the diffusion of the conversation and the emergent discourses. The discourse was first developed and shared by a homogeneous cluster that later created varied discourses over a number of hours.…”
Section: Conversation Patternsmentioning
confidence: 99%
“…Anstead and O'Loughlin (2011) revealed that 20% of those commenting on a TV program on Twitter were responsible for more than 50% of the content. Maireder and Schlögl (2014) reconstructed the dynamics of a debate about sexism in Germany, examining the hashtag #aufschrei (#outcry) to visualize networked publics, mapping the diffusion of the conversation and the emergent discourses. The discourse was first developed and shared by a homogeneous cluster that later created varied discourses over a number of hours.…”
Section: Conversation Patternsmentioning
confidence: 99%
“…The hashtag also plays a role in aggregating tweets with specific themes or events, allowing the same hashtag users to identify, discuss, and connect with each other. The development of 'hashtagging' practices by Twitter users to mark and categorize themes produces what Maireder and Ausserhofer [7] describe as theme networks-semantic networks represented in digital object text [8]. The motivation of Twitter users in tagging (hashtagging) is twofold, firstly for the purpose of structured archiving (organizational), as well as for social and communicative goals [9].…”
Section: Introductionmentioning
confidence: 99%
“…Scholars who examine collective behavior on social media commonly frame online collective activity within theoretical perspectives developed to describe offline phenomena, such as communities (e.g., Albrechtslund, 2010;Velasquez, 2012) and publics (e.g., Maireder & Schlögl, 2014;Shklovski & Valtysson, 2012;Tremayne, Zheng, Lee, & Jeong, 2006). While this approach has its merits in terms of its ability to provide a theoretical foundation for a relatively new field of study, its potential of describing online phenomena is limited due to differences between online and offline spaces.…”
Section: Introductionmentioning
confidence: 99%